Strengthening the Character Values of Cooperation and Responsibility through the STAD Learning Model in Islamic Education (PAI) Instruction at SMK Karya Teknika Colomadu, Karanganyar - Difa'ul Fikri Jayyid; Sukari (At Turots: Jurnal Pendidikan Islam, 2026)
This study employed a quantitative descriptive approach with a quasi-experimental design to examine the effectiveness of the Student Teams Achievement Division (STAD) learning model in strengthening the character values of cooperation and responsibility in Islamic Education (PAI) learning. The objective of this research was to analyze the extent to which the implementation of the STAD model contributes to the development of students’ cooperative attitudes and sense of responsibility in the learning process. The research was conducted at SMK Karya Teknika Colomadu, Karanganyar, involving 30 students as the research sample. Data were collected through observation sheets, questionnaires, and documentation. The indicators of cooperation included active participation, mutual assistance, and group engagement, while responsibility indicators covered task completion, learning discipline, and accountability during group activities. Data analysis was carried out using descriptive statistical techniques in the form of percentages. The results showed that the application of the STAD learning model had a positive impact on students’ character development. The level of cooperation among students reached 83.3%, categorized as high, while the responsibility character value achieved 80.0%, also classified as high. Overall, the strengthening of character values through the STAD model in PAI learning reached an average percentage of 81.7%, indicating that the STAD model is effective in fostering cooperation and responsibility among vocational high school students